Studies on the structures, cytotoxicity and apoptosis mechanism of 8-hydroxylquinoline rhodium(iii) complexes in T-24 cells. (13th May 2016) - Zhang, Hai-Rong; Liu, Yan-Cheng; Chen, Zhen-Feng; Meng, Ting; Zou, Bi-Qun; Liu, You-Nian; Liang, Hong
Abstract : Two rhodium(iii ) complexes showed good cytotoxicity. The underlying investigation of the apoptosis mechanism suggested that the mitochondrial apoptotic pathway was involved. Abstract : Two rhodium(iii ) complexes (Rh(OQ)3 (1) and Rh(BrQ)2 (CH3 OH)Cl (2), HOQ = 8-hydroxyquinoline, HBrQ = 5-bromo-8-hydroxyquinoline) of 8-hydroxylquinoline were synthesized and characterized. By MTT assay, the in vitro cytotoxicity of complexes1 and2, compared with HOQ, HBrQ and cisplatin, was evaluated towards a series of tumor cell lines as well as the normal liver cell line HL-7702. Complexes1 and2 showed higher cytotoxicity against the tested tumor cell lines than the corresponding ligands, among which T-24 was the most sensitive cell line for complexes1 and2 (IC50 = 13.42 μM for1, 18.91 μM for2 ). Compared with cisplatin, complex1 exhibited higher cytotoxicity against T-24 cells but lower cytotoxicity against HL-7702(IC50 = 15.93 μM). Considering the better cytotoxicity of complex1 than complex2 against T-24 cells, the underlying anticancer molecular mechanisms were also investigated. DNA interaction studies revealed that complex1 interacted with ct-DNA mainly via an intercalative binding mode. Further investigation of intracellular mechanisms revealed that complex1 caused G2 phase cell cycle arrest and induced T-24 cell apoptosis in a dose-dependent mode. Targeting the mitochondrial pathway, the apoptotic mechanism in T-24 cells treated with1 was studied by ROS detection, intracellular Ca 2+ concentration measurements and caspase-9/3 activity assay, which suggested that complex1 induced T-24 cell apoptosis by the disruption of mitochondrial-related mechanisms.